Repair of common arterial trunk type I after previous pulmonary artery banding: technical considerations - Karolczak, Maciej A.; Grabowski, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Aorto-pulmonary window technique in type I truncus arteriosus repair is a valuable alternative to pulmonary trunk division and neoaortic wall reconstruction. The technique used in infants after previous pulmonary artery banding is illustrated, described and discussed.